THE EFFECT OF INTERFACING TYPE ON THE FINISHED RESULT OF PANELED CIRCLE SKIRT USING BRIDAL MATERIAL - Zhafirah Zhafirah; Puspaneli Puspaneli (Gorga : Jurnal Seni Rupa, 2024)
A paneled circle skirt is a type of skirt that expands, consists of several pieces and is shaped like a star fruit. In making a paneled circle skirt so that the panel looks upright and has volume, it needs to be coated with interfacing. Interfacing is a material that is paired between clothes to make a part of clothing look strong and neat, therefore the selection of the right coating material will affect the finished result of the paneled circle skirt. This study aims to describe the finished results of paneled circle skirts using woven and non-woven interfacing in terms of skirt volume, skirt flatness and skirt shape stability aspects and describe the effect of interfacing type on the finished results of paneled circle skirts using bridal materials. The type of research conducted is experimental research. The object of the research is a paneled circle skirt that uses woven interfacing, namely trubenais and non-woven interfacing, namely pelon. The research instrument was a questionnaire with a likert scale. The data used was primary data obtained by distributing questionnaires to 15 panelists. The data analysis techniques used are descriptive statistics and inferential statistics. Based on data analysis, there is an effect of interfacing type on the finished result of the paneled circle skirt, the finished result of the paneled circle skirt using woven interfacing (trubenais) is obtained an overall percentage value of 86% categorized as very suitable while the finished result of the paneled circle skirt using non-woven interfacing (pelon) is obtained an overall percentage value of 65% categorized as suitable.